Mengenal dan memahami fiqh difabel (penyandang disabilitas) - Tias, Nadila Aprilia Ning (Maliki Interdisciplinary Journal, 2024)
This article uses the method of introducing and understanding what Fiqh on Disability is. Every teaching and law that comes from the Qur’an and As-Sunnah has great wisdom and the principle is rahmah (compassion) to each of His creatures, who are physically and intellectually different. This shows that Islam is a religion of rahmatan lil’alamin. Islam often gives special attention to people with disabilities who have special limitations compared to ordinary people. Therefore, the conditions and abilities of humans who carry out the Shari’a are of great concern. Nowadays, the law for people with disabilities has become very important. Facilities dedicated to people with disabilities are increasingly optimized as technology and times progress. In this rahmatan lil’alamin form of Islamic teaching, the formulation of fiqh will continue to address the needs of Muslims, especially for people with disabilities today and in the future.